A facile method to prepare reduced graphene oxide with nano-porous structure as electrode material for high performance capacitor. Issue 48 (28th April 2016) - Yang, Nian; Xu, Xiaoyang; Li, Lingzhi; Na, Heya; Wang, Huan; Wang, Xuefang; Xing, Fubao; Gao, Jianping
Abstract : Reduced graphene oxide (M-rGO) with enhanced electrochemical performance has been prepared. Electrochemical analyses show that the M-rGO has a maximum capacitance of 577.4 F g −1 at 1 mV s −1 with excellent rate performance. Abstract : A facile method to prepare reduced graphene oxide (M-rGO) nanosheets with enhanced electrochemical performance has been established by using Mg powder as the reductant. The structural, morphological and electrochemical properties of the M-rGO have been characterized. The prepared M-rGO possesses well-developed nano-porous structure and superior surface characteristics. Electrochemical analyses show that the M-rGO has a maximum specific capacitance of 577.4 F g −1 at the scan rate of 1 mV s −1, and an excellent rate performance of 324.9 F g −1 at 1 V s −1 . The CV curves of M-rGO can keep rectangular in shape even at a scan rate of 500 mV s −1 without obvious distortion. Such outstanding electrochemical performances of M-rGO can be attributed to both the presence of nano-pores in M-rGO and the pseudocapacitance arising from residual oxygen-containing functional groups.